2020
DOI: 10.2147/ott.s266541
|View full text |Cite
|
Sign up to set email alerts
|

<p>Role of miRNA-424 in Cancers</p>

Abstract: microRNA (miRNA) is an important part of non-coding RNA that regulates gene expression at a posttranscriptional level. miRNA has gained increasing interest in recent years, both in research and clinical fields. miRNAs have been found to play an important role in various diseases, particularly cancer. Aberrant miR-424 expression is found in several tumors where they can function as either oncogenes or tumor-suppressor genes. Meanwhile, miR-424 is also affected by the reorganization of many other non-coding RNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…Thus, they are widely implicated in many disorders such as cardiovascular disease, neural disease, and cancer. 59,60 During heart development, miR-322/miR-503 has been shown to drive early cardiac progenitor cells toward cardiomyocyte lineage, although the underlying mechanism is undetermined. 61 Our current study demonstrates that HDAC3 represses miR-322 and miR-503 expression to induce the expression of several major growth ligands including FGF9 and IGF2 for ventricular wall cardiomyocyte proliferation (Figure 7F).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they are widely implicated in many disorders such as cardiovascular disease, neural disease, and cancer. 59,60 During heart development, miR-322/miR-503 has been shown to drive early cardiac progenitor cells toward cardiomyocyte lineage, although the underlying mechanism is undetermined. 61 Our current study demonstrates that HDAC3 represses miR-322 and miR-503 expression to induce the expression of several major growth ligands including FGF9 and IGF2 for ventricular wall cardiomyocyte proliferation (Figure 7F).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA is related to many biological functions, such as proliferation, development, differentiation, apoptosis, and metabolism [ 12 ]. Many studies showed that abnormal miRNA expression is significantly linked to tumorigenesis, and it is now a hot research area [ 13 , 14 ]. The most prevalent subtype of lung cancer is adenocarcinoma, which has a high worldwide morbidity and mortality rate [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-322 and miR-503 regulate many fundamental processes such as cell proliferation, death, differentiation, metabolism, and stress response. Thus, they are widely implicated in many disorders such as cardiovascular disease, neural disease, and cancer 71,72 . During heart development, miR-322/miR-503 has been shown to drive early cardiac progenitor cells toward cardiomyocyte lineage, although the underlying mechanism is undetermined 73 .…”
Section: Discussionmentioning
confidence: 99%